Peluang Implementasi Sunset Clauses Legislation dalam Pembentukan Undang-Undang di Indonesia - Elsa Wulandari; Dirga Achmad (Program Studi Hukum Tata Negara, Institut Agama Islam Negeri Parepare, 2025)
This article discusses the potential for the sunset clauses legislation method to be applied in the formation of laws in Indonesia, which has previously been implemented in several countries (the United States, Switzerland, South Korea, Germany, and Australia) to address regulatory issues. This is interesting to study because the legal framework in Indonesia, particularly laws, is overlapping and unimplementable due to over regulation. Therefore, the author found three problem mappings to be discussed: the urgency of sunset clauses legislation in Indonesia, a comparative study of the application of sunset clauses legislation in other countries, and how sunset clauses legislation is regulated in the legal norm system when implemented in the formation of laws in Indonesia. The problem mapping will be studied comprehensively using normative methods with conceptual, statutory, case, and comparative approaches. The type of data used is secondary data obtained through literature studies which are then analyzed qualitatively. Keywords: Sunset Clauses Legislation, Laws, Over regulation